Kindergarten Teachers’ Skills in Initial Assessment for Special Needs Identification: Keterampilan Guru Taman Kanak-Kanak dalam Penilaian Awal untuk Identifikasi Kebutuhan Khusus - Sukesi; Pujaningsih; Ishartiwi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Early childhood education plays a crucial role in shaping children’s development, yet teachers often struggle to conduct systematic initial assessments for identifying children with special needs. Specific Background: Despite inclusive education being a global and national priority, many kindergarten teachers lack the necessary skills, leading to delayed interventions and missed opportunities for tailored support. Knowledge Gap: Previous training programs remain mostly theoretical, one-directional, and disconnected from real classroom contexts, with limited research combining guided training and Project-Based Learning (PjBL) for early assessment in preschool settings. Aims: This study aimed to improve kindergarten teachers’ skills in conducting initial assessments of children with special needs through guided training using a PjBL approach. Results: Using collaborative School Action Research in two cycles, findings showed significant improvements in teachers’ cognitive, affective, and psychomotor competencies, with more structured assessment practices and reflective attitudes toward inclusive education. Novelty: The study introduces an integrated training model that extends the application of PjBL from instructional design to early assessment, an area rarely explored in early childhood education research. Implications: The proposed model provides a replicable framework for education authorities and early childhood institutions to strengthen teacher competence in inclusive education, contributing to sustainable improvements in service quality and supporting broader educational equity goals.Highlight : Teachers’ ability in early assessment improved through guided training with PjBL. Competence increased across cognitive, affective, and psychomotor aspects. The model supports sustainable inclusive education practices. Keywords : Initial Assessment, Children With Special Needs, Kindergarten Teachers, Project-Based Learning, Guided Training, Inclusive Education